QUOTES BUDI UTOMO SEBAGAI SARANA PENGUAT KESADARAN NASIONAL - Brigida Intan Printina (Universitas Galuh, 2019)
This article aims to describe the Budi Utomo Quotes Based on Canva Applications for National Awareness Strengthens. In order for the struggle of the Budi Utomo movement to be interpreted in depth by generations, the visual graphic media was chosen to strengthen the national awareness of the generation. This is in line with the basic principles of Budi Utomo's movement, namely the primacy of mind or mind in terms of education. The research method in this article is qualitative descriptive. The writing results describe the process and results of the use of visual graphic media that photographed Budi Utomo's movement with the aim of strengthening the national awareness of Indonesian youth so as to be able to integrate past struggles as a capital